2011
DOI: 10.1111/j.1742-6723.2011.01455.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Prehospital fluid management in traumatic brain injury

Abstract: The early management of patients who have sustained traumatic brain injury is aimed at preventing secondary brain injury through avoidance of cerebral hypoxia and hypoperfusion. Especially in hypotensive patients, it has been postulated that hypertonic crystalloids and colloids might support mean arterial pressure more effectively by expanding intravascular volume without causing problematic cerebral oedema. We conducted a systematic review to investigate if hypertonic saline or colloids result in better outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 23 publications
(77 reference statements)
0
20
0
3
Order By: Relevance
“…No studies have reported better survival and functional outcomes over the use of isotonic crystalloids. [30] Further to this, a multicenter randomized control trial (RCT) of 1087 patients (15 years or older with blunt trauma who did not meet the criteria for hypovolemic shock) with severe TBI (GCS 8 or less) showed that even the initial resuscitation with hypertonic saline or hypertonic saline/dextran, compared with normal saline, were found to be comparable in terms of 6-month neurologic outcome or survival. [31] However, this study was terminated by the data and safety monitoring board after randomization of 1331 patients.…”
Section: Methodsmentioning
confidence: 99%
“…No studies have reported better survival and functional outcomes over the use of isotonic crystalloids. [30] Further to this, a multicenter randomized control trial (RCT) of 1087 patients (15 years or older with blunt trauma who did not meet the criteria for hypovolemic shock) with severe TBI (GCS 8 or less) showed that even the initial resuscitation with hypertonic saline or hypertonic saline/dextran, compared with normal saline, were found to be comparable in terms of 6-month neurologic outcome or survival. [31] However, this study was terminated by the data and safety monitoring board after randomization of 1331 patients.…”
Section: Methodsmentioning
confidence: 99%
“…These studies have not consistently shown a benefit for hypertonic solutions. [16][17][18] No randomized controlled clinical trials directly comparing the pre-hospital use of LR and NS in injured patients have been conducted to date.…”
mentioning
confidence: 99%
“…However, recent clinical trials have failed to demonstrate the superior efficacy of HTS over other fluid resuscitation strategies [23][25]. The heterogeneity in the trial designs, treatment regimen, read-outs, and the low number of patients enrolled for each study have precluded a definitive consensus and the debate remains largely open.…”
Section: Discussionmentioning
confidence: 99%